Trends in the Development of Oil and Gas Complex - A. P. Garnov; V. Yu. Garnova; N. P. Tishkina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The home oil and gas complex plays an important role in Russian economy. The article deals with finding the key trends in the development of oil and gas complex and analyzing the acute challenges facing oil and gas enterprises. The authors came to the conclusion that in today’s conditions the oil and gas complex encounters severe competition on global market due to high volatility of oil prices and growth in extraction cost. The complicated macro-economic situation caused the shortage of finance. In the coming decade the distribution of different power resource consumption will considerably change. To secure their competitiveness enterprises of the oil and gas complex should revise strategies of positioning on power resource market. The authors propose to use three possible ways of developing oil and gas companies: to extract mineral resources at max rate, to diversify, to start development of renewable sources of power. Irrespective of the selected way of development oil and gas companies should watch closely the three important aspects: reforming the portfolio structure focusing on strengths and new fields of growth, introducing digital technologies and attracting competent experts.